Shear strength of soft clay reinforced with acrylonitrile butadiene styrene (ABS) column - N Thevagar, Nedunchelian; Muzamir, Hasan (Penerbit UTM Press, 2023)
The troublesome soil that many geotechnical engineers encounter in the sector is clay soil. It presents a major danger to the foundations of light structures. Granular columns have proved beneficial in resolving foundation stabilisation and settling issues, making soft clay more appropriate for foundation building. This study aims to determine whether adding acrylonitrile butadiene styrene (ABS) to kaolin clay increases its shear strength. The physical, mechanical, and morphological properties of the materials used in this research (i.e., kaolin and ABS) must first be identified. The soft clay kaolin was strengthened with ABS columns and tested using the unconfined compression test (UCT) and the unconsolidated undrained test (UUT). The diameter of the columns used in this study was 8, 12, and 16 mm, while the penetration depth ratio used was 0.5, 0.75, and 1.0. The highest improvement in shear strength occurred at a height penetration ratio of 0.5 with values of 102.94%, 48.56%, and 50.02%. The UCT results demonstrated a decrease in the volume of the replacement ratio, followed by an increase in the height of the column. The UUT was conducted to evaluate the soft clay's shear strength when reinforced with an ABS column. The cell pressure used was 50, 100, and 200 kPa with the same column diameter specification as the UCT. The friction angle, υ, increased significantly from 8.92% to 18.21%. Furthermore, there was an improvement in cohesiveness, c, which increased from 4.54% to 45.45%. The results show that installing ABS columns improves the strength and compressibility of clay samples.